2003
DOI: 10.1046/j.1365-2141.2003.04601.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA microarray analysis of stage progression mechanism in myelodysplastic syndrome

Abstract: Summary. Myelodysplastic syndrome (MDS) is a clonal disorder of haematopoietic stem cells. Despite the high incidence of MDS in the elderly, effective treatment of individuals in its advanced stages is problematic. DNA microarray analysis is a potentially informative approach to the development of new treatments for MDS. However, a simple comparison of 'transcriptomes' of bone marrow mononuclear cells among individuals at distinct stages of MDS would result in the identification of genes whose expression diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 25 publications
1
38
2
2
Order By: Relevance
“…PIASy was shown to be hypermethylated in patients with MDS-derived AML (see above) [60]. We could not find any reports on PIAS hypermethylation in de novo AML.…”
Section: Hypermethylation Of Stat Inhibitors In Acute Leukemiascontrasting
confidence: 41%
See 2 more Smart Citations
“…PIASy was shown to be hypermethylated in patients with MDS-derived AML (see above) [60]. We could not find any reports on PIAS hypermethylation in de novo AML.…”
Section: Hypermethylation Of Stat Inhibitors In Acute Leukemiascontrasting
confidence: 41%
“…However, SOCS1 hypermethylation was detected in MDS patient samples [58,59]. Finally, PIASy mRNA was studied in blasts from 37 patients; it was present in stem cells from 13 MDS patients in the early phase (refractory anemia) of the disease but its expression was suppressed in samples from patients in the more advanced stages (nine with refractory anemia with excess of blasts and 13 MDS associated leukemia) of the disease [60] to suggest that methylation of STAT regulators may be involved in the transformation of MDS to AML.…”
Section: Hypermethylation Of Stat Inhibitors In Myelodysplastic Syndrmentioning
confidence: 99%
See 1 more Smart Citation
“…Examining gene expression profiles has been extremely useful for establishing different phenotypes in cancer. [1][2][3] Various microarray profiles in mood disorder have been reported that use different microarray platforms, analysis methodology, regional differences, agonal factors and brain pH. [4][5][6][7][8][9][10][11][12][13][14] Presumably, a substantial heterogeneity in the pathophysiology of mood disorder coupled with small sample sizes and small fold changes contributes to the lack of consistency among the findings.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…The deregulation of several proteins like RB (Ledl et al, 2005), SENP1 (Veltman et al, 2005), PIAS3 (Wang and Banerjee 2004), PIASy (Ueda et al, 2003), SUMO1 (Villalva et al, 2002), SUMO2 (Lee 2004) etc. by SUMOylation and its involvement in cancers of different kinds provides an opportunity to exploit SUMOylation as anticancer drug target.…”
Section: Sumoylation and Anticancer Drugsmentioning
confidence: 99%